Evaluation of website information provided by paediatric surgery centres in Australia and New Zealand. Issue 9 (26th January 2019) - Meiyappan, Vivek; Little, Timothy A.; Jackson, Paul
Abstract : Background: Hospital websites are an important source of information for patients, parents and healthcare providers. There are currently no standardized recommendations for the information provided on paediatric surgery websites. We aimed to assess the information available on each hospital website, in Australia and New Zealand, which provides paediatric surgical care. Methods: Google search was performed of the 16 paediatric surgical centres in Australia and New Zealand to determine whether they had a hospital website and to assess its contents. The presence of patient fact sheets and clinical practice guidelines was recorded. Access to contact information, hospital Facebook page and Twitter handles were noted. Results: We found that 11 (69%) centres had a specific paediatric surgical section to the hospital website, all provided contact information. Five centres (31%) had paediatric‐specific guidelines available for health professionals. Six websites (37.5%) provided health information sheets on common paediatric surgical conditions. Facebook and Twitter facilities were present on the majority of the websites (75%). Conclusion: The internet presence of paediatric surgery in Australia and New Zealand is sparse. One‐third of centres do not have hospital web presence. The availability of clinical guidelines and patient information sheets on hospital websites is limited. Our findings would suggest that improvement and increase in the internet presence of paediatric surgery in Australia and New Zealand is needed. Abstract : This is the first study to evaluate the quality of paediatric surgical information provided in hospital websites within Australia and New Zealand. One‐third of centres do not have a hospital webpage. Our findings suggest that an improvement in internet presence of paediatric surgery in Australasia is needed.